Public Management in Städten und Gemeinden Verwaltungsreformen und deren Auswirkungen in der Schweiz - Haus, Alexander (Modernisierung des öffentlichen Sektors ("Gelbe Reihe"), 2023)
Private-sector management practices have been used by cities and municipalities in their public administration for several years. Yet, little is known about the effects of these management reforms, especially in a culturally heterogeneous environment. On the basis of a national survey covering 1,868 Swiss cities and municipalities, information was collected and analysed on the management reforms applied and their impact on public administration performance and democracy. The results of this interdisciplinary study show that management reforms in Switzerland have had positive effects, regardless of the linguistic and cultural context in which they were enacted. However, the use of private-sector approaches is more common in the German-speaking part of Switzerland and in cities.